2015
DOI: 10.1155/2015/487159
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Anxiety among Patients with Multiple Sclerosis Attending the MS Clinic at Sheikh Khalifa Medical City, UAE: Cross-Sectional Study

Abstract: Depression and anxiety are reported to be prevalent in patients with MS, with prevalence rates ranging from 20% to 50%. Unfortunately, the rates, patterns, and risk factors are not well studied in our Middle East region, and, to our knowledge, not at all in UAE. Using standardized screening tools, we observed that 17% and 20% of 80 patients seen in MS clinic had scores consistent with major depression and anxiety disorders, respectively, at a rate that was not statistically different when compared to age and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 27 publications
7
29
2
Order By: Relevance
“…In our study, the highest levels of depression, stress, and anxiety were observed in married patients, which is in line with the results of Alsadi et al(2015) [20]. However, Barzegar et al (2017) found no significant association between marital status and depression among MS patients in Iran [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the highest levels of depression, stress, and anxiety were observed in married patients, which is in line with the results of Alsadi et al(2015) [20]. However, Barzegar et al (2017) found no significant association between marital status and depression among MS patients in Iran [22].…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study and those of the above study were similar with respect to the prevalence of anxiety and depression. The results of the study by Alsaadi et al (2015) in Emirates showed from 80 MS patients, 17% had severe depression and 20% had moderate Anxiety. Moreover, no significant relationship was found between anxiety and depression and variables age, sex, and education [20].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only one pilot study has been conducted on the link between depression and MS in the UAE. 15 However, that study did not find an increased rate of depression, unlike several studies in other Arab countries, 15,16 possibly due to the small sample size and single-center nature of the study. The present study aimed to examine these findings in a multicenter study with a larger sample size and explore the differences in depression as a function of demographic variables and disease characteristics.…”
Section: Patient Characteristicscontrasting
confidence: 55%
“…The very moment of receiving the diagnosis is a stressful, life-changing event for the majority of patients and their families. To improve the quality of life of the patients, recognition of this emotional and cognitive burden is crucial in regards to all parties involved (7) (8).…”
Section: Introductionmentioning
confidence: 99%